The effects of dance intervention on clinical symptoms and cognitive deficits in hospitalized patients with chronic schizophrenia: a randomized controlled trial - Gujing Li; Hui He; Kexin Gao; Yuanyuan Yu; Yayun Liu; Tianhuan Li; Ping Xi; Frank Pollick; Jing Lu; Lixue Yin; Dezhong Yao; Mingjun Duan; et al. (PeerJ)
Background Schizophrenia is a severe mental disorder that imposes significant social burdens. Traditional treatmens, however, have limited effectiveness in addressing negative symptoms and cognitive deficits. Recent studies have indicated interventions promoting sensorimotor integration may offer potential benefits for schizophrenia treatment. The current study aimes to investigate the effects of dance training as an intervention for patients with chronic schizophrenia. Methods This study recruited 34 individuals with schizophrenia, who were randomly allocated to either a dance intervention group (n = 18) or an aerobic exercise group (n = 14) for a 3-month program including fifty-minute sessions three times per week. Clinical symptoms were assessed using the Positive and Negative Syndrome Scale (PANSS) and Nurses’ Observation Scale for Inpatient Evaluation (NOISE). Cognitive function was evaluated using the MATRICS Consensus Cognitive Battery (MCCB). Meanwhile, physiological indicators were also collected to explore the underlying physiological effects of the dance intervention. All measurements were taken before and after the interventions. Results The PANSS total scores (P < 0.01**), PANSS negative scores (p < 0.001**), NOISE score (p < 0.001**), MCCB cognitive scores, and physiological indicators were significantly changed after the intervention in both groups compared with baseline. Post-hoc analysis revealed notable improvements in the specific cognitive subscales, including the Continuous Operation Test-identical pairs (CPT-IP, p = 0.026*), Hopkins Verbal Learning Test-Revised (HVLT-R, p = 0.019*) and the physiological indicators Cystatin C (CYS-C, p = 0.037*) in the dance intervention group. Additionally, significant correlation were found between PANSS positive score and Total Bilirubin (TBIL) (r = 0.449, p = 0.028*), as well as between CPT-IP and Cystatin C (CYS-C) (r = 0.501, p = 0.008**) were found in both groups. Conclusion While both interventions resulted in improvements in clinical symptoms and cognitive function, the dance intervention specifically enhanced attention and verbal memory. Dance and aerobic exercise induced different changes in physiological indicators, which might be the physiological basis for improvements in clinical symptoms and cognitive function.